Financial analysis of bankruptcy - Sýkora, Igor; Janda, Karel; Fučík, Vojtěch; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2017)
Thesis “Financial analysis of bankruptcy” is divided into three sections. First section focus on agency problems and its implications to bankruptcies. Bankruptcy with soft budget approach prefer reorganization of firm instead of liquidation. Implementation of rescue culture in Czech Insolvency Act is described. Second section focuse on financial analysis of firm in order to reveal approaching bankruptcy. Liquidity, debt, performance and efficiency ratios are introduced. Moreover, bankruptcy and solvency models such as Altman’s z score, IN Financial Analysis and Kralicek’s Quick test are described into detail. Final section analyse bankruptcy of Czech lottery leader Sazka in order to find out what is the originator of it. Analysis consist of description of it insolvency proceedings involving all above mentioned points of view – legal point, soft budget constraint and financial analysis.
Vedoucí práce: Karel Janda
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: bankovnictví a pojišťovnictví [obor dipl. práce]; diplomové práce; master's theses